1969
DOI: 10.1007/bf01247355
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of rock salt in openings mined for the disposal of radioactive wastes

Abstract: Summary --Zusammenfassung --Résumé Deformation of Rock Salt in Openings Mined for the Disposal of Radioactive Wastes.With the storage of high-level radioaetive waste in salt struetures, unique mine stability problems will oeeur as a result of the elevated temperatures. To prediet flow in rock salt, seale models of salt pillars and their surrounding rooms were fabrieated from eores taken in the Carey salt mine, Lyons, Kansas. Tests were eondueted at temperatures of 22.5 e, 60 o , 100 °, and 200°C for axial load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1979
1979
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 4 publications
0
7
0
1
Order By: Relevance
“…tures is possible both for uniaxial and triaxial testing conditions. This type of testing has been performed for many rocks, including salt (Serdengecti and Boozer, 1961;Lomenick and Bradshaw, 1969).…”
Section: -10mentioning
confidence: 99%
See 2 more Smart Citations
“…tures is possible both for uniaxial and triaxial testing conditions. This type of testing has been performed for many rocks, including salt (Serdengecti and Boozer, 1961;Lomenick and Bradshaw, 1969).…”
Section: -10mentioning
confidence: 99%
“…The parabolic law is a purely empirical relationship taken from laboratory experiments. Misra and Murrell , 1965;Carter and Heard, 1970 : = AT Linear Law None Dolomite Sandstone Granodiorite Misra and Murrell , 1965 = AT" Parabolic Law Salt Lowenick and Bradshaw, 1965 andStarfield and McClain, 1973 1/ strain rate:…”
Section: Temperature Lawsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model has been used with different empirical constants to model salt creep (Boresi and Deere, 1963;Lomenick and Bradshaw, 1969;Thoms et al, 1973). Reviews of the various simple functional forms ε 1 (t) and ε 2 (t) can assume, are found in Jaeger and Cook (1979), Hansen (1983), andJaeger et al (2007).…”
Section: Inelastic Deformation Effectsmentioning
confidence: 99%
“…The behavior of salt rock under static loading has been thoroughly studied [3][4][5][6][7][8]. The effect of cyclic loading on the mechanical properties of geologic material has long been recognized.…”
Section: Literature Reviewmentioning
confidence: 99%